Development of Animated Video-Based Learning Media on Stage Make Up Material at SMKN 3 Probolinggo - Triwidarti, Endah; Faidah, Mutimmatul; Puspitorini, Arita; Usodoningtyas, Sri (PT. Riset Press International, 2025)
Learning media is vital in supporting students' practical and exciting learning process, especially in learning that requires understanding specific concepts and competencies. The development of this animated video-based learning media is based on the need for innovative learning media development and following technological developments, especially in the context of stage makeup learning. This research also aims to determine 1) the development of animated video-based learning media, 2) the feasibility of animated video-based learning media, and 3) students' responses to using animated video-based learning media. This research uses a quantitative approach using the R&D (Research & Development) method and Four-D (4-D) research design. The 4-D stages adopted in this study include Define, Design, and Development. The data obtained validate the feasibility of animated video-based learning media and student responses. The research subjects were 26 Skin and Hair Beauty students at SMKN 3 Probolinggo. The data collection method used was a validation test and questionnaire. The analysis method uses averages to determine the feasibility of learning media and learner responses. Based on the results of data analysis of the feasibility of animated video-based learning media, very valid criteria were obtained, namely with an average of 89.78% for media experts and 88.89% for material experts. Students' response to the development of animated.